ORGANIZATION OF SEMINARS WORK FOR STUDENT WITH USING MEDIA INSTRUMENTS OF IKPE - Tarasich, Ю.Г.; Spivakovska, Є.О. (Journal of Information Technologies in Education (ITE), 2014)
Any training takes place in the learning environment that provides an educational process that creates a space of interaction of the student and the teacher. This environment is a information and communication pedagogical environment (IKPE). Using IKPE funds at classroom avoids the monotony of their conduct, to raise students' interest in the learning process and intensify their activities. Seminars helps to ensure a student the basic knowledge, helps develop logical thinking, to form beliefs. In line with the growth of teachers' understanding of the need to introduce information and communication technology and electronic media for educational purposes in the learning process,as well as the students get used to the appropriate provision of information, we are seeing increased of the quality of educational services and thus the quality of knowledge. Constant monitoring of IKPE in universities let us to evaluate not only the quantity and quality of the implementation of new technologies in the educational environment of the university,but also to prioritize of their development. Evaluation of the results of research indicates an increase in the level of ICT using and therefore, in a sense, of improving the quality of education in compliance with the rapid process of society informatization .